The temporary protection directive is dead, long live the temporary protection directive! Indispensability of the temporary protection scheme in the eu legal landscape - Mazur, Sylwia Katarzyna (2022)
On 24 February 2022 an unprovoked Russia attacked Ukraine, causing a mass movement of displaced persons fleeing Ukraine and in need of international protection. On 4 March 2022, the European Council established the existence of a mass influx of displaced persons, and with that for the first time in the history activated Directive 2001/55/EC, providing quick and effective assistance to people fleeing the war. This action has become an exception in the treatment of forcibly displaced persons arriving at the European Union (EU) borders. The main objective of this study is to explore the complementary position that temporary protection occupies within the Common European Asylum System (CEAS), where it serves not only as a tool to provide protection to persons forcefully displaced en masse, but also to ease the pressure on national asylum systems. What makes the presented research even more interesting is the fact that although temporary protection in the EU had been regulated (at least in theory) for over twenty years, it is still highly politicized and dependent on the will of European leaders. This article combines theoretical considerations (analysis of international law and European law) with a case study of actions taken (and not taken) by the EU during the 2022 migratory pressures.